Electrochemical energy storage in an organic supercapacitor via a non-electrochemical proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Mendhe, Rahul Mahadeo; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Chemical Science, 2024)
Contrary to conventional beliefs, we show how a functional ligand that does not exhibit any redox activity elevates the charge storage capability of an electric double layer via a proton charge assembly. Compared to an unsubstituted ligand, a non-redox active carboxy ligand demonstrated nearly a 4-fold increase in charge storage, impressive capacitive retention even at a rate of 900C, and approximately a 2-fold decrease in leakage currents with an enhancement in energy density up to approximately 70% via a non-electrochemical route of proton charge assembly. Generalizability of these findings is presented with various non-redox active functional units that can undergo proton charge assembly in the ligand. This demonstration of non-redox active functional units enriching supercapacitive charge storage via proton charge assembly contributes to the rational design of ligands for energy storage applications.

Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.